IMPLEMENTATION OF PENSION FUND DISBURSEMENT SERVICES USING AN AUTHENTICATION APPLICATION TO ASSESS SERVICE QUALITY FOR RETIRED CIVIL SERVANTS (STUDY AT BANK KALIMANTAN BARAT, KUBU RAYA BRANCH) - Ryan Windiatmoko; Pudjianto; Ahmad Tohardi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the implementation of pension fund disbursement services using authentication applications on the quality of service for retired Civil Servants at Bank Kalimantan Barat Kubu Raya Branch, so that the success of service quality and performance of Bank Kalimantan Barat Kubu Raya Branch in implementing digital services through authentication applications must be implemented as optimally as possible in order to minimize the disruption of authentication services to pension participants. The background of this study is based on the fact that there are still suboptimal pension fund disbursement processes caused by the lack of socialization carried out by pension service providers and the activation of authentication applications that have not been understood by pension participants. The study uses a qualitative descriptive approach with the research model used being an intrinsic case study from Charles O. Jones to assess the organization, understanding and implementation of pension fund disbursement services using authentication applications. Data collection techniques include observation, documentation, and in-depth interviews with employees and pensioners at Bank Kalimantan Barat Kubu Raya Branch. The results of the study indicate that the first aspect of the organization is carried out with the availability of sufficient human resources during peak service hours and the number of human resources that are adjusted to the volume of services and following the SOP in working thus can conduct an analysis of HR needs in service. Second, the understanding aspect carried out by Bank Kalimantan Barat Kubu Raya Branch in providing pension fund disbursement services in the form of providing counseling and socialization to customers regarding the procedures for implementing pension fund disbursement services using authentication applications at Bank Kalimantan Barat Kubu Raya Branch is quite clear. Third, the implementation aspect of authentication application services at Bank Kalimantan Barat Kubu Raya Branch Bank Kalimantan Barat Kubu Raya Branch has various strategies and policies in pension fund disbursement services to ensure the process runs smoothly and in accordance with applicable regulations aimed at improving the security and efficiency of transactions and access to banking services in the form of biometric authentication. Suggestions that can be given are training for Bank employees in implementing the authentication process and socialization to pensioners aimed at improving understanding of carrying out the authentication process.